Clinical trial registration. Issue 7605 (4th June 2007) - Laine, Christine; Horton, Richard; DeAngelis, Catherine D; Drazen, Jeffrey M; Frizelle, Frank A; Godlee, Fiona; Haug, Charlotte; Hébert, Paul C; Kotzin, Sheldon; Marusic, Ana; Sahni, Peush; Schroeder, Torben V; et al.
Abstract : Looking back and moving ahead